ANALISIS MOTIVASI KERJA KARYAWAN BAGIAN ADMINISTRASI PTPN XIII KEBUN PARINDU - B31109098, R. Bellarmino Dayana (Jurnal Manajemen Update, 2016)
The purpose of this study is to analyze the motivation of employees in the administration in PTPN XIII Parindu garden. The method used in this research is descriptive statistics. Samples of respondents using the administrative staff of 50 respondents PTPN XIII Parindu garden. The data can be used questionnaires with respondents using five options, Strongly Agree, Agree, doubtful, Disagree, Strongly Disagree with each point is worth of 5 to 1. The results that can be achieved by respondents respectively answered by the respondents were selected in accordance with the existing indicators are 5 options With the option on indicators of the achievements reached 24% of respondents strongly agreed and 54% answered agree on the first question and the second question 16% answered strongly agree and 74% answered agree. And on the second indicator recognition of others as much as 18% and 76% answered strongly agree and agree on the first question, while on the second question respondents answered as much as 30% strongly agree and 52% disagree. In the third indicator responsibility as much as 50% of each of the answers agree and strongly agree on can be the first question on the second question as much as 16% and 66% who answered strongly agree and agree. On indicators of job satisfaction by 22% and 76% answered strongly agree and agree on the first question, while on the second question by 30% and 62% answered strongly agree and agree. In the last indicator chance to go forward with the data on the first question and the second to reach 12% and 66% answered strongly agree and agree, while 40% and 54% answered strongly agree and agree on the answer points. With the data obtained indicate if the administrative staff PTPN XIII have a good motivation to work for its own employees and also for the company's future. Keywords: employee motivation, PTPN XIII